2016
DOI: 10.1155/2016/1342056
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Corneal Wavefront Aberrations in Dry Eye Patients after Treatment with Artificial Lubricant Drops

Abstract: Purpose. To evaluate the corneal aberration changes in dry eye patients after treatment with artificial eye drops. Methods. Thirty mild to moderate dry eye patients treated with artificial eye drops and twenty comparable dry eye patients were recruited as controls. Anterior corneal aberrations over 3 mm and 5 mm analytical zones including total, 3rd to 5th high order aberrations (HOAs), spherical aberration (SA), and vertical (V-coma) and horizontal coma (H-coma) obtained from corneal topography data at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…In their study, tear hyperosmolarity was found to be associated with lower repeatability of keratometry measurements. 11 Artificial eye drops therapy in dry eye patients has been shown to be effective in increasing corneal optical quality by improving the higher order aberrations 8 and topographic ectasia parameters 16 of the anterior corneal surface. Zemova et al 17 showed that there was no association between dry eye and topographic changes in keratoconus patients by Pentacam topography device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, tear hyperosmolarity was found to be associated with lower repeatability of keratometry measurements. 11 Artificial eye drops therapy in dry eye patients has been shown to be effective in increasing corneal optical quality by improving the higher order aberrations 8 and topographic ectasia parameters 16 of the anterior corneal surface. Zemova et al 17 showed that there was no association between dry eye and topographic changes in keratoconus patients by Pentacam topography device.…”
Section: Discussionmentioning
confidence: 99%
“… 7 When the tear film is disrupted, the optical surface becomes irregular and may cause additional aberrations or unpredictable keratometry measurements. 8 , 9 , 10 , 11 Dry eye is one of the most common entities in ophthalmology practice; previous studies have reported its prevalence as ranging between 3.9% and 16.7%, with higher rates in the elderly and women. 12 , 13 As dry eye and other eye pathologies may coexist, it is essential to know the repeatability of topography measurements among dry eye patients.…”
Section: Introductionmentioning
confidence: 99%
“…Deterioration of the tear film can result in irregular corneal surface that affects the visual quality. Higher order aberrations are focused in the anterior cornea than in the posterior corneal surface when the tear interface is compromised [ 67 ]. Dry eye is also characterized by reduction of superficial corneal epithelial microvilli, and the conversion of corneal epithelial phenotype to Keratin 10 positive epidermal phenotype which results in tear film instability [ 68 , 69 ].…”
Section: Ocular Surface Microenvironment Change In Dry Eyementioning
confidence: 99%
“…Some of the most important functions of the precorneal tear film include lubricating the ocular surface and providing a smooth, regular optical surface for the eye. 11 , 12 Blinking of the eyelids prevents breaking up of the tear film; however, the eyelids must remain open during cataract surgery. As a consequence, several environmental factors (e.g., the use of anesthetics and topical mydriatic agents, long surgery, high temperature and/or low humidity in the operating room, and the intensity of the microscope illumination) may compromise lubrication of the ocular surface and leave the cornea hazy.…”
Section: Discussionmentioning
confidence: 99%